KEPERCAYAAN MEMODERASI KUALITAS PELAYANAN ISLAMI TERHADAP LOYALITAS PELANGGAN PADA KLINIK PENGOBATAN HERBAL DI PONOROGO - Ika Susilawati; Pramono Hari Adi (Jurnal Ilmiah Ekonomi Islam, 2022)
This study examines the marketing of services that focus on herbal medicine clinics. Herbal medicine clinic is a service business that has special characteristics in its services, so the purpose of this study is to explore the impact of Islamic service quality on patient loyalty with trust as a moderating variable. The method used is quantitative with SEM analysis tool, with AMOS application. This study answers the 3 hypotheses proposed, in which the results of the path coefficients indicate that the three hypotheses are accepted and support previous research. The implication of this research is that patient trust is the main thing in a service business, so to achieve that trust, service providers must provide quality Islamic services so that there is a long-term relationship with patients, namely patient loyalty. Keywords: Loyalty, trust, clinic, Compliance, sharia